FUNDAMENTAL PRINCIPLES OF INTERNATIONAL LEGAL REGULATION OF OCCUPATIONAL SAFETY AND HYGIENE - Dreval, Yu.; Tsymbal, В.; Malko, О.; Sharovatova, О.; Petryshchev, А.; Artemev, S. (Municipal economy of cities. Series: «Economy science», 2023)
The issue of the essence and peculiarities of international legal and organizational and technical regulation of the sphere of safety and occupational hygiene was considered. The significance of the reasons and prerequisites, which collectively led to a renewed understanding of the activities of the International Labor Organization and the sphere of occupational safety and hygiene in today's complex conditions, was noted. It was found that the fundamental basis of the modern activity of this organization was the study of fundamental principles and rights in the world of work. The place of the fundamental conventions of the ILO in the implementation of principles and rights in the field of labor is defined. The directives that form the legal basis of the European Union in the field of human health and safety at work are defined. Two types of auxiliary normative documents of different nature are considered, which are considered relevant for taking into account important aspects of labor activity. The conclusion regarding the current state and prospects for the development of the fundamental principles of international legal and organizational and technical regulation of occupational safety and hygiene is substantiated. Emphasis is placed on the expediency and necessity of attributing the concept of occupational safety and hygiene to international labor standards and fundamental principles and rights in the field of labor. New trends in the international legal and organizational and technical regulation of the sphere of occupational safety and hygiene, which are manifested in the countries of the European Union and Ukraine, have been identified. It has been established that the emergence of legislation, which contains the norms of collective agreements on the establishment of benefits related to the safety and occupational hygiene of older workers - persons of pre-retirement age who have a long working experience, should be considered a new phenomenon in the labor law of the European Union countries. It was noted that the European Strategy for the Working Environment proposed innovations: to introduce regional occupational health and safety commissioners in EU countries and to strengthen sanctions against employers guilty of violating the rules of safety at work. It was found that, in addition to the international legal regulation of the ILO and the EU, it carries out organizational and technical, which regulates risk-oriented management of occupational safety and hygiene, which is aimed at assessing occupational risks according to the proposed methods, which are general and not adapted to the specifics of various branches of the economy. Therefore, the methodology for assessing occupational risks of the ILO was improved, which contains a volumetric matrix that is three-component, and the same technique allows for the assessment of residual risk.